The Model of Dynamic Inelastic Behavior of Brittle Solids Based on the Concept of Finite Fracture Time - Grigoriev A. S. Aleksandr; Shilko E. V. Evgeny; Skripnyak V. A. Vladimir; Psakhie S. G. Sergey Grigorievich (2018, 2018)
Title screen